Two layered approaches integrating harmony search with genetic algorithm for the integrated process planning and scheduling problem. (May 2021) - Wu, Xiuli; Li, Jing
Abstract: To solve the integrated process planning and scheduling problem (IPPS) effectively, we propose a nested approach for the single objective IPPS problem. In the outer layer of the approach, harmony search (HS) algorithm is utilized to determine the processing sub-route of manufacturing features, and the static scoring method and the dynamic scoring method of the processing sub-route of manufacturing features are put forward to guide the search of the outer layer. Synchronously, in the inner layer, genetic algorithm (GA) is employed to determine machine assignment and operation sequence. Besides, the selection operator in the inner layer and the minimum spanning tree clustering method are integrated to increase the population diversity. To make up the deficiency of the nested approach for solving the large-scale I-IPPS problem, an upper and lower layer approach with a quick estimation method is presented, too. Finally, the best combination of the improvement strategies for the nested approach and the best combination of harmony search strategies for the upper and lower layer approach are determined with experiments. The results for testing benchmark instances prove the effectiveness of the proposed approaches.